A case of SRSF2 mutation in chronic lymphocytic leukemia. (2016) - Garza, Eduardo; Del Poeta, Giovanni; Martínez-Losada, Carmen; Catalano, Gianfranco; Borgia, Loredana; Piredda, Maria Liliana; Fabiani, Emiliano; Gattei, Valter; Lo-Coco, Francesco; Noguera, Nélida I.
Abstract: Chronic lymphocytic leukemia (CLL) is characterized by extremely variable clinical course indicating substantial differences in the biology of the disease. Molecular characterization provides new insights useful for treatment decision making. We report on a patient diagnosed with CLL, whose disease was characterized by episodes of rapid progression and disease stabilization, and in which a SRSF2 gene mutation was identified in the absence of other commonly known mutations of CLL. To the best of our knowledge this is the first case of SRSF2 gene mutation ever reported in CLL. Highlights: We report a CLL patient with SRSF2 gene mutation in the absence of other mutations. CLL case responsive to therapy with episodes of rapid progression and long remissions. This is the first case of SRSF2 gene mutation ever reported in CLL.